An Empirical Study on Natural Disaster Risk and Its Impact on Rural Bank Stability and Third-Party Funds in Indonesia - Nisa, Chaerani; Ichwani, Tia; Kurniawati, Dewi; Rahmawati, Novita (FEB-UP Press, 2024)
This study aims to analyze the impact of disaster risk on the stability and the ability of rural Indonesia to mobilize third-party funds. The data used in this research comprises information from 1,502 rural banks across 283 cities or regencies in 37 provinces. Observations of these rural banks were conducted over five years, from 2019 to 2023, yielding an unbalanced panel data with 7,226 observations. The methodology employed in this study is panel data analysis using a fixed effect model. The results indicate that disaster risk has a negative and significant effect on the stability of rural banks. In contrast, the ability of rural banks to mobilize third-party funds is not affected by disaster risk. A more in-depth analysis reveals that differences in rural banks' characteristics also influence the impact of disaster risk. Rural banks located on Java Island and those not owned by the government are more significantly impacted in terms of financial stability. Meanwhile, government-owned rural banks are more affected by their ability to mobilize third-party funds. These findings suggest that rural banks located on Java Island and those not government-owned should implement better risk mitigation measures, such as collaborating with larger financial institutions for asset management, to reduce the negative impact of disaster risk on economic stability.